Islamic Financial Technology Adoption and MSME Performance: Integrating Literacy, Compliance, Accessibility, and Leadership - Zulfadli Hamzah; Astri Ayu Purwati; Rosyidi Hamzah (Journal of Applied Engineering and Technological Science (JAETS), 2026)
This study aimed to analyze the effect of Sharia financial literacy, Sharia compliance, technology accessibility, and Islamic leadership on the performance of MSMEs in Riau – Indonesia, with the mediation of Sharia Financial Technology Adoption and the moderation of government regulations. This research employed a quantitative study approach using a survey methodology. The sample consisted of 500 MSMEs in Riau that had used services from Sharia financial institutions and had been operating for at least one year. The analytical technique employed was Structural Equation Modeling (SEM) with the assistance of SmartPLS 4 software. The results showed that Sharia financial literacy, technological accessibility, and Islamic leadership had a significant effect on Sharia financial technology adoption and MSME Business performance. Furthermore, Sharia fintech adoption significantly mediated the effect of these three variables on the performance of MSMEs. Conversely, the effect of Sharia compliance on Sharia financial technology adoption and MSME performance was not significant, nor was the moderating effect of government regulations, which failed to strengthen the relationship between Sharia financial technology adoption and MSME business performance.